Health outcome implications and prevention in communities based on race/ethnicity, gender, smoking status, and biological factors in COVID-19 and its variants. (29th March 2022) - Mathur, Sunil; Mathur, Shreya; Monahan, Laura
In this article, we aim to investigate the variable effects of COVID-19 on public health and shed light on factors responsible for disproportionate mortality rates among different people. We investigate preventive activities that have been in practice and explore health promotion activities that can be applied to a population base by public health practitioners. The most significant effects of COVID-19 are among non-Hispanic blacks and Latino individuals. Smokers had twice the prevalence of COVID-19 compared to non-smokers. Several factors such as age, diabetes, obesity, hypertension, male sex, and race/ethnicity significantly affect health outcomes in people exposed to COVID-19. Young African Americans are dying at a higher rate than their counterparts in other groups due to COVID-19. Understanding the factors behind the variable effects of COVID-19 among different people may allow public health officials to develop and implement public policies and interventions to mitigate adverse health outcomes effectively.